Research of production technology as a factor influencing the time of the product assembly cycle - V. S. Ponomareva; O. V. Khomutskaya (Омский научный вестник)
Nowadays the organization of domestic serial production of high-tech products requires a lot of time. On the one hand, the reason is the restructuring of logistics chains with foreign suppliers, on the other hand, the building of cooperation in the country. For example, the duration of the implementation of promising production projects in the space industry is still years. Factories are changing approaches in the organization of work – one of the main ways to influence the duration of production is to reduce the time of their own production cycle. As a rule, the analysis of the organization of serial production begins with the final assembly, which determines the tact of work for all other sites that produce components. When evaluating the effectiveness of the organization of assembly production, criteria and factors are determined. The time of the product assembly cycle is taken as the efficiency criterion. It is necessary to determine the degree of significance for each factor and understand their mutual influence on each other. The purpose of the research is to develop a unified system of factors affecting the cycle, and a method based on this system for evaluating the effectiveness of the organization of assembly production. The article considers the technological process as a factor affecting the product assembly cycle.